Berperan Dalam Pembangunan SDM, Saatnya Insentif Guru Ngaji Bersumber Dari APBN - Baidowi, Achmad (Syura: Journal of Law, 2024)
Well-consolidated human resource development must be supported by an adequate, targeted and equitable budget so that there is an increase in quality in the national education system in our country. There are 3 (three) parties in the national education system, namely students, education personnel, and educators. As the name implies, students are pupils or students who will undergo education or the learning process. Meanwhile, education personnel are parties who dedicate themselves and are appointed with the aim of supporting the implementation of education. While educators are education personnel who have qualified as teachers, lecturers, tutors, instructors, or the like, who participate in organizing education. Quran teachers take part as educators for the non-formal sector who already have qualifications and have participated a lot in organizing education in Indonesia. This study uses a qualitative approach with the method used in this study is the normative research method. The author's analysis uses conceptual analysis. The results of this study The Koran teacher as an educator is to direct students towards maturity with a perfect human personality, and the Koran teacher as a leader is able to control themselves, students and the community related to social problems. Budget allocation from the APBN is something that should be an effort to pay attention, appreciate and improve the welfare of Koran teachers